System-activity method in crime investigation - N.A. Podol'nyy (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The detection and disclosure of all crimes committed is the goal that law enforcement agencies are tasked with. Criminal prosecution must be unavoidable for all persons who have committed a crime. In order to implement this, an appropriate methodological framework is needed, the elements of which are the methods used by law enforcement agencies, including investigators. One of such methods that can increase the effectiveness of detection, disclosure and investigation of crimes is the system activity method. In this regard, the purpose of the research conducted and based on the article was to determine the system-activity method and the patterns of its use during the ongoing investigation of crimes. Materials and methods. The methods of analysis and synthesis, induction and deduction were used in the research based on the proposed article. The theory of activity developed in psychology was also of methodological importance. Results. When investigating crimes committed by organized groups, traditional methods of identifying incriminating data (information) are not effective enough, since they focus only on establishing the circumstances related to the crime committed and do not take into account the circumstances of the behavior of the alleged perpetrator outside of the crime committed by him. Conclusions. To increase the effectiveness of the ongoing investigation and expose the person responsible for it, it is advisable to use a systematic activity method, which allows, based on knowledge of the personality characteristics of a particular person, to determine the likelihood of her involvement in the crime.